2019
DOI: 10.1103/physrevphyseducres.15.020137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of out-of-class science and engineering activities on physics identity and career intentions

Abstract: The number of physics bachelor's degrees that are awarded in the United States annually is small compared to most other science, technology, engineering, and mathematics fields, and only about one-fifth of these degrees are awarded to women. Understanding the influence of students' science and engineering experiences on career choices is critical in order to improve future efforts to increase the number of physics majors and the participation of women. In this work, we use a physics identity framework to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
(77 reference statements)
0
34
1
Order By: Relevance
“…In terms of specific findings that address the hypotheses posed earlier, we found that for both first year and senior female physics undergraduates, interest is mediated by recognition and performance/competence; interest does not have a direct effect on physics identity 1 . This is in contrast with earlier studies for broader student populations (with many different disciplinary interests and aspirations) which found interest to have a direct effect on physics identity while performance/competence had an indirect effect mediated by both recognition and interest (Figure 1; Godwin et al, 2016; Lock et al, 2019; Potvin & Hazari, 2013). Another recent model of students in introductory calculus‐based physics courses at one institution found that all three constructs had a direct effect on physics identity, although both interest and performance/competence had smaller effects than recognition (Kalender et al, 2019).…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…In terms of specific findings that address the hypotheses posed earlier, we found that for both first year and senior female physics undergraduates, interest is mediated by recognition and performance/competence; interest does not have a direct effect on physics identity 1 . This is in contrast with earlier studies for broader student populations (with many different disciplinary interests and aspirations) which found interest to have a direct effect on physics identity while performance/competence had an indirect effect mediated by both recognition and interest (Figure 1; Godwin et al, 2016; Lock et al, 2019; Potvin & Hazari, 2013). Another recent model of students in introductory calculus‐based physics courses at one institution found that all three constructs had a direct effect on physics identity, although both interest and performance/competence had smaller effects than recognition (Kalender et al, 2019).…”
Section: Discussioncontrasting
confidence: 94%
“…Students who felt able to perform and competent, needed to be recognized or become interested in order to see themselves as a “physics person.” These results were consistently replicated across multiple domains (mathematics, physics, and science generally) in different studies with broad college student populations (not just physics majors; Cribbs, Hazari, Sonnert, & Sadler, 2015; Godwin et al, 2016). In physics, this has also been studied at both the high school and university level for students in classes with broad student populations with similar findings (Cheng et al, 2018; Godwin et al, 2016; Lock et al, 2019).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations